Brain vs computer the challenge of the century - Fillard, Jean-Pierre (World Scientific Pub., 2017)
The brain is a very complex organ and we are just beginning to understand how it works; many things remain mysterious and can lead to surprises. Would a transfer of minds in a machine be possible? Would the computer be capable of a self, nonneuromorphic intelligence? These questions are now open. Who will win? We do not know yet. But it is certain that many things are going to change in our lives in the very near future.